2018
DOI: 10.29238/jtk.v14i2.370
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Kegiatan Pelayanan Asuhan Kesehatan Gigi Dan Mulut Terhadap Pengetahuan Sikap Status Kesehatan Gigi Dan Mulut Siswa Sekolah Dasar

Abstract: Service Activities Dental and Oral Health Care is part of the School Dental Health Enterprises (UKGS) which aims to improve the knowledge, attitude and the ability to behave in the field of healthy living oral health. These activities include outreach, shared toothbrushes and dental examinations, but oral health care has no knowledge, so the researchers are interested to know the difference before and after the service activities of oral health care on knowledge, attitude, oral health status elementary student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…Behavior is also a person's response to a stimulus in action. It is evident in the form of practices that others can easily observe or see (Sirat, 2015). This study result supports previous studies, which concluded a significant correlation between brushing behavior and the incidence of dental caries (Evyana, Rohmawati, and Perdana, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Behavior is also a person's response to a stimulus in action. It is evident in the form of practices that others can easily observe or see (Sirat, 2015). This study result supports previous studies, which concluded a significant correlation between brushing behavior and the incidence of dental caries (Evyana, Rohmawati, and Perdana, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…There is no guarantee that attitudes will be displayed in behavior. A prior investigation also found that even though students had good knowledge of dental and oral health, they did not maintain dental and oral health well (Sirat, 2015).…”
Section: Discussionmentioning
confidence: 92%
“…Data yang digunakan pada penelitian adalah data primer dan data sekunder. Data primer ini diambil dari pemeriksaan DMF-T. Dimana untuk komponen D (Decayed) yaitu semua gigi yang mengalami karies dan masih bisa ditambal, tumpatan dengan karies (karies sekunder), pemasangan crown karena karies dan tambalan sementara, komponen M (Missing) yaitu gigi hilang karena karies, gigi karies yang tidak bisa ditambal dan indikasi pencabutan, sedangkan komponen F (Filling) yaitu gigi yang telah ditambal karena karies atau tambalan tanpa karies (Gultom and Laut, 2018). Data sekunder diperoleh dari tata usaha sekolah yaitu data jumlah murid dan juga biodata murid MTs Nurul Ikhlas Tabing Kecamatan Koto Kampar Hulu Kabupaten Kampar Provinsi Riau.…”
Section: Metode Penelitianunclassified
“…CR tools designed explicitly for intraoral dental examinations have been widely used in dental health, including in Indonesia (Nuraisya, 2023). However, in reality, the results displayed by a unique CR dental tool from one of the brands circulating in Indonesia during a demonstration of the tool at the Pramita Main Clinic, Martadinata Bandung branch, were not yet able to provide a digital image display that could be processed such as 100% and 200% image enlargement.…”
Section: Introductionmentioning
confidence: 99%